The Role of Rac GTPase in Dendritic Spine Morphogenesis and Memory - Costa, Joana Freitas; Dines, Monica; Lamprecht, Raphael (Frontiers in Synaptic Neuroscience, 2020)
The ability to form memories in the brain is an important process needed for daily functions and its impairment is associated with human mental disorders. Evidence indicates that long-term memory (LTM) related processes such as its consolidation, extinction and forgetting involve changes of synaptic efficacy produced by alterations in neural transmission and morphology. Modulation of the number of dendritic spines and their morphology has been proposed to contribute to alterations in neuronal transmission mediating such LTM related processes. Rac GTPase activity is regulated by synaptic activation and it can affect spine morphology by controlling actin-regulatory proteins. Recent evidence shows that changes in Rac GTPase activity affect memory consolidation, extinction, erasure and forgetting and can affect spine morphology in brain areas that mediate these behaviors. Altered Rac GTPase activity is associated with abnormal spine morphology and brain disorders. By affecting Rac GTPase activity we can further understand the roles of spine morphogenesis in memory. Moreover, manipulation of Rac GTPase activity may serve as a therapeutic tool for the treatment of memory-related brain diseases.